Effectiveness of a Behavioral Intervention vs. Standard Care for Pediatric Obesity: A Randomized Controlled Trial - Oneeb, Afshin; Olayiwola, Aminat; Pahlajrai, Nirmaldas; Ihsan Ullah; Khan, Sheheryar Alam (Indus Journal of Bioscience Research, 2025)
Background: Pediatric obesity is a growing public health issue, leading to long-term health risks such as diabetes, cardiovascular disease, and psychological distress. Standard care approaches, which primarily focus on general lifestyle advice, often show limited success. This study examines whether a structured behavioral intervention is more effective than standard care in managing childhood obesity. Methods: This randomized controlled trial was conducted at Jinnah Teaching Hospital from September 1, 2024, to February 28, 2025. A total of 110 children aged 6 to 14 years with obesity were randomly assigned to either a behavioral intervention group (n=55) or a standard care group (n=55). The intervention group participated in a structured program involving dietary education, physical activity sessions, and behavioral counseling, while the standard care group received general weight management advice. Primary outcomes included changes in BMI, body fat percentage, and waist circumference. Secondary outcomes assessed metabolic markers, dietary habits, physical activity levels, and psychological well-being. Data were analyzed using SPSS, with a p-value of